2024
DOI: 10.3390/jcm13071837
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Assessment of Mortality Risk and Hospital Stay Duration in Hospitalized Patients with COVID-19 Treated with Remdesivir: A Machine Learning Approach

Antonio Ramón,
Andrés Bas,
Santiago Herrero
et al.

Abstract: Background: Despite advancements in vaccination, early treatments, and understanding of SARS-CoV-2, its impact remains significant worldwide. Many patients require intensive care due to severe COVID-19. Remdesivir, a key treatment option among viral RNA polymerase inhibitors, lacks comprehensive studies on factors associated with its effectiveness. Methods: We conducted a retrospective study in 2022, analyzing data from 252 hospitalized COVID-19 patients treated with remdesivir. Six machine learning algorithms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Machine learning comparative studies, which include extreme gradient boosting, support vector machine, linear discriminant analysis, random forest and logistic regression, are starting to gain traction in predictive modeling for healthcare-for instance, regarding the risk of stroke [54], knee osteoarthritis diagnosis [55] and mortality risk and hospital stay duration in hospitalized patients with COVID-19 treated with Remdesivir [56]. The latter two works showed that extreme gradient boosting provided the highest accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning comparative studies, which include extreme gradient boosting, support vector machine, linear discriminant analysis, random forest and logistic regression, are starting to gain traction in predictive modeling for healthcare-for instance, regarding the risk of stroke [54], knee osteoarthritis diagnosis [55] and mortality risk and hospital stay duration in hospitalized patients with COVID-19 treated with Remdesivir [56]. The latter two works showed that extreme gradient boosting provided the highest accuracy.…”
Section: Discussionmentioning
confidence: 99%